Comportamento de oviposição de Aedes aegypti em área endêmica de dengue do estado de São Paulo - Dibo, Margareth Regina (2004)
The strategy to contain the vector of Dengue fever in the state of São Paulo is centered around a reduction in breeding places and by chemical controls. To obtain better results in the reduction of the vectorial density it is important to incorporate other measures in the routine approach. Egg traps are considered to be preventative and control measures of Aedes aegypti, however, there are no studies that define the favorite egg-laying locations in residences. The utilization of an infusion of Panicum maximum in traps increases its attractiveness to vector females and increases the number of eggs collected. This study aims to contribute to techniques by using traps to evaluate the number of weeks this infusion remains attractive to females. More importantly, it aims to assess the egg-laying behavior of the Aedes aegypti and Aedes albopictus populations in Mirassol, a town situated in the region of São José do Rio Preto, Brazil. Traps with egg-collecting paddle were installed in 200 houses in 20 blocks giving a total of 10 houses to each block. Half of the blocks were chosen at random for the installation of traps baited with the infusion and in the other half, traps with ordinary water were installed. Two egg-traps were placed inside the house (bedroom and living room) and two outside (one under cover and the other in the open). Weekly visits were made from September to December 2002, to analyze all the traps, collecting the existing sticks and leaving new ones. In the laboratory the viable and nonviable eggs on the sticks were counted. Positive sticks were considered to be those on which eggs were found and these were correlated with the type of trap, infusion or water, the location of the trap within the house and the number of weeks after the start of the trial. A sample of these sticks was placed in water, to hatch the larvae with the aim of identifying the species. The mean numbers of eggs and larvae of the Aedes aegypti and Aedes albopictus were calculated and associated with the location within the house, the type of trap used, infusion or water, and the week number. Analyzing the number of positive sticks, and the mean number of eggs on the traps, it was evidenced that the traps with infusion were more attractive/stimulating for egg-laying for females of the genera Aedes than those with water in the first three weeks of exposition. The uncovered outdoor traps were the most favored location for egg-laying during the entire study period; in second place were the outdoor ones under cover. High values of the Spearman correlation coefficients and p-values less than 0.004 demonstrated a strong correlation between the positivity and the mean number of eggs, indicating that one variable predicts the other. From the analysis of the hatched larvae, Aedes aegypti were identified on 99.6% (CI 95%: 99.04 99.84) of the sticks and Aedes albopictus on 1.8% (CI 95%: 1.19 2.70) of them. In Mirassol the probability of finding eggs of Aedes aegypti on any one stick under these circumstances is greater than 99%.